Heterogenitas Orang Keturunan Cina (Tionghoa) di Indonesia Dalam Perspektif Sosial-Budaya - Lan, Thung Ju (Paradigma: Jurnal Kajian Budaya, 2012)
The issue of heterogeneity of Chinese Indonesians is often seen as something simple, because the general view tends to focus on traditional categorization such as race/ethnic group, religion and occupation. In fact, the development of the society which was supported by technological development has produced the variable of ‘class’ and global influences that diversify various social and economic activities so that the world of business and life within the ‘local’ and/or ‘national’ realms as a whole becomes very complex. As a result, the heterogeneity of Chinese Indonesians should be seen, not only through traditional categorization, but also according to the political history of Indonesian nation-state, the dynamics of relations between China, as the country of origin, and Indonesia as the country of settlement, the scattering of Chinese in Indonesian territory that consists of a number of big and small islands, as well as the Chinese individual’s perspective on how the Chinese should be located in the Indonesian society.